1984
DOI: 10.1161/01.hyp.6.3.315
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma norepinephrine in young patients with essential hypertension under three sodium intakes.

Abstract: SUMMARY Increased sympathetic nerve activity may play an important role in the pathogenesis of essential hypertension. It is well known that both dietary sodium intake and age influence the plasma norepinephrine (NE) concentration. The present study was undertaken to evaluate the effects of age on sympathetic nerve activity in patients with essential hypertension and normal control subjects under low-, regular-, and high-sodium regimens (mean 24-hour sodium excretions: 30 ± 4,116 ± 7, 280 ± 15 mEq, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…There are many reports on comparisons of plasma NE in hypertensive and normotensive subjects at rest and during exercise or standing, but the results have not been conclusive. Plasma NE levels are influenced by the levels of sodium intake, age, and a family history of hypertension (Christensen & Brandsborg 1973;McDermott et al 1974;Masuo et al 1983Masuo et al , 1984Munger et al 1986). In the present study, therefore, we compared plasma NE levels at rest, on standing and after a certain amount of liquid meal, between male hypertensive and normotensive subjects of similar age with similar dietary intakes of sodium and potassium.…”
Section: Discussionmentioning
confidence: 99%
“…There are many reports on comparisons of plasma NE in hypertensive and normotensive subjects at rest and during exercise or standing, but the results have not been conclusive. Plasma NE levels are influenced by the levels of sodium intake, age, and a family history of hypertension (Christensen & Brandsborg 1973;McDermott et al 1974;Masuo et al 1983Masuo et al , 1984Munger et al 1986). In the present study, therefore, we compared plasma NE levels at rest, on standing and after a certain amount of liquid meal, between male hypertensive and normotensive subjects of similar age with similar dietary intakes of sodium and potassium.…”
Section: Discussionmentioning
confidence: 99%
“…A decreasing ability with age to handle exogenous blood pressure-affecting factors such as salt intake, extracellular volume, and serum proteins may also be of importance. 22 Several previous studies 23 " 29 have investigated possible age-related changes in the production of catecholamines. The results are conflicting, but the majority of these studies conclude that increased norepinephrine levels are balanced by a decrease in receptor sensitivity.…”
mentioning
confidence: 99%
“…Some investigators (2,3) have also reported that plasma NE clearance was increased in renal failure. However, it is also known that plasma NE, as an index of sympathetic nerve activity, increases with aging (4) and that plasma NE responses to change is position is increased (5,6).…”
Section: Discussionmentioning
confidence: 99%